Perception of user opinions towards Sharia mobile banking applications in Indonesia based on comments on Google Play Store - Rosanti, Cholisa; Artanto, Fenilinas Adi; Saputra, Reza Edi (LPMP Imperium, 2025)
This research aims to evaluate user perceptions of the performance of m-banking applications at Islamic banks by analyzing user reviews on the Google Play Store from 4 July 2023 to 4 July 2024. The research results show that the BSI Mobile and Jago Syariah applications are the most downloaded and have the most reviews, indicating a high number of active users. Analysis using the Bag of Words (BoW) and Support Vector Regression (SVR) methods shows excellent performance in predicting user sentiment, with an accuracy of more than 90% on six sharia m-banking applications, where the Aladin Syariah application achieved the highest accuracy of 98. 54%. Research findings show that positive perceptions of the app's ease of use contribute to user loyalty. At the same time, complaints regarding the login and registration process must be improved. Positive reviews such as